The Impact of Special Interests on Preferential Tariff Concessions by the United States - Ray, Edward John (The Review of Economics and Statistics, 1987)
This paper provides empirical evidence on the relative impact of the generalized system of preferences, adopted in 1975, and the Caribbean Basin Initiative, adopted in 1983, on the pattern of U.S. imports of manufactured goods from the target areas at the four-digit level in 1984. Imports from Brazil, Mexico, South America, the Caribbean Basin, and all eligible countries are each analyzed. The author provides evidence that existing preferential agreements have failed to offset the bias in U.S. protection against competitive exports from developing countries and explains why one might have predicted such an outcome. Copyright 1987 by MIT Press.